The Findings Of The Governors Of The Turkestan General-Governor’s Office - Ergashev, Bakhtiyar Ergashevich; Rasulova, Durdona Bakhronovna; Amirkulov, Zhasur Bahtiyorovich; Mamatkulova, Farangiz Orzukulovna; Khasanova, Zulkhumor Djalolitdinovna (The journal of contemporary issues in business and government, 2021)
History of Turkestan in the second half of the 19th and at the beginning of the 20th century was the actual and scientific investigative problem. The main factor in learning this epoch was that the territory of the country was occupied by the Russian Empire and general imperial rules of the government which was in operation were maintained throughout the country on the whole space of Central Asia. The methods of regulation were carried out in two directions: military and civilian. In written sources they are identified as military and democratic governance. For the complete exploration of the essence of the colonial management, we need to study and learn the main sources of information, in which the main dominant materials of the office work was chancellery of Turkestan general governorship. The article is devoted to the history of the ruling chancellery of the general governorship, which ruled the whole process of the chancellery work in provision of the executive power in Turkestan. The main sources are the materials of the fund “I-1” of the Central State Archive of the Republic of Uzbekistan. Chronological frame captures the period from 1867 to 1917.